Markets, trade, and institutions division - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
IFPRI’s Markets, Trade, and Institutions Division (MTID) provides innovative, evidence-based policy solutions to help drive inclusive economic growth, reduce poverty, and ensure food security worldwide through a more efficient food system.